2023
DOI: 10.1186/s12905-023-02318-y
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome awareness among females in the UAE: a cross-sectional study

Abstract: Background Polycystic Ovarian Syndrome (PCOS) is a common hormonal disorder affecting females of reproductive age. Clinical guidelines recommend following the diagnostic criteria of PCOS based on an appropriate assessment of the patient’s clinical presentation. Sufficient awareness among the population will prompt females to seek medical attention when necessary. This study aimed to assess knowledge and awareness about PCOS among females above the age of 18 years in the United Arab Emirates (UA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The relationship between knowledge about PCOS and various demographic factors, such as age, educational level, marital status, nationality, and BMI, did not significantly impact PCOS knowledge. This finding contrasts with previous research indicating that education level could influence PCOS knowledge [ 17 ]. However, participants with PCOS diagnosis exhibited significantly higher knowledge levels, suggesting that awareness campaigns should target both diagnosed and undiagnosed individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…The relationship between knowledge about PCOS and various demographic factors, such as age, educational level, marital status, nationality, and BMI, did not significantly impact PCOS knowledge. This finding contrasts with previous research indicating that education level could influence PCOS knowledge [ 17 ]. However, participants with PCOS diagnosis exhibited significantly higher knowledge levels, suggesting that awareness campaigns should target both diagnosed and undiagnosed individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…(Figure 4) Most participants agreed that a fiber-rich diet helps prevent PCOS while 128 participants selected meditation and 109 participants chose weight loss. (Table 4) 6), 2(1-3), 2(0-2), 2(1-3) and 11 (8)(9)(10)(11)(12)(13)(14) respectively. (Table 5, Figure 7) All in all, 76.15% of participants fell under the non-aware group compared to only 23.85% of participants who demonstrated good awareness (>60%) (Figure 8)…”
Section: Resultsmentioning
confidence: 99%
“…For statistical significance, p value of less than 0.05 was considered statistically significant. The study of Balkis Zaitoun, et al [8] observed that 21.7% of participants had sufficient awareness of the syndrome. Taking this value as reference, the minimum required sample size with 5.5% margin of error and 5% level of significance is 216 participants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, there is a lack of understanding regarding PCOS due to cultural taboos and stigmas around discussing menstruation or female reproductive health concerns in an open manner. More similar kind of study also found that most of the participants had poor knowledge and health-related practices toward PCOS [22,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%